1992
DOI: 10.1007/bf00378278
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure in indoor firing ranges

Abstract: Higher air lead levels (time-weighted average 660, range 112-2238 micrograms/m3) were measured in firing ranges where powder charges were employed than in ranges where air guns were used (4.6, range 1.8-7.2 micrograms/m3); levels in the latter were in turn higher than those in ranges used for archery (0.11, range 0.10-0.13 micrograms/m3). Twenty-two marksmen who used powder charges had significantly increased blood lead levels during the indoor shooting season (before: median 106, range 32-176 micrograms/l; af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Shooters in Sweden using large calibre handguns on an outdoor range during summertime and on an indoor range during wintertime had a signiWcant increase (P = 0.0001) in BLLs after the indoor season. BLLs were measured at the end of the summer shooting season and at the end of the winter shooting season (Svensson et al 1992). Another Swedish study showed also a positive correlation of BLLs among police oYcers with the number of rounds annually Wred (Löfstedt et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Shooters in Sweden using large calibre handguns on an outdoor range during summertime and on an indoor range during wintertime had a signiWcant increase (P = 0.0001) in BLLs after the indoor season. BLLs were measured at the end of the summer shooting season and at the end of the winter shooting season (Svensson et al 1992). Another Swedish study showed also a positive correlation of BLLs among police oYcers with the number of rounds annually Wred (Löfstedt et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…DOE security guards are required to maintain proficiency with firearms. Previous studies of firing range exposures have reported relatively high lead exposures (Svensson et al 1992, Goldberg et al 1991, Valway et al 1990). DOE security workers are exposed to internal combustion engine exhaust as a result of vehicle inspections conducted prior to allowing automobiles and trucks to enter sites.…”
Section: Security Workersmentioning
confidence: 94%
“…La información sobre el tema es relativamente abundante, y sólo remarcaremos los casos más significativos. La peor situación se produce principalmente en campos cubiertos («indoor») [24][25][26][27] , donde la concentración de plomo en el aire puede alcanzar 26 hasta los 2.238 µg/m 3 , cuando la actual legislación española y europea marca un máximo de 150 µg/m 3 como valor límite ambiental para la exposición diaria (VLA-ED) 28 . El problema afecta a los tiradores, lo sean estos por motivos recreativos 24,26,29 o profesionales 30 , pero igualmente a trabajadores y otro personal que frecuente estos lugares 24,25,27 .…”
Section: Vía Inhalatoriaunclassified